Tingkat Pengetahuan, Sikap Dan Tindakan Siswa-Siswi Sekolah Menengah Atas Terhadap Acquired-Immunodeficiency Syndrome - Angel, Pretty; Nababan, Kristo A.; Hutasoit, Eka Samuel P. (Universitas Methodist Indonesia, 2024)
Background: The problem of HIV/AIDS is a major problem that threatens Indonesia and many other countries around the world. Currently there is not any country free from HIV/AIDS. Since the beginning of the HIV/AIDS became epidemic, nearly 78 million people in all over the world have been infected with HIV and about 39 million people have died from HIV. WHO estimates that 0,8% of people worldwide aged 15-49 years live with HIV. Method: The purpose of this study is to determine the level of knowledge, attitude, and action in SMA Negeri 1 Kabanjahe against AIDS. This research uses descriptive method with cross sectional approach. Samples are students of class X & XI IPA counted 136 people with slovin formula, where respondents obtained by using simple random sampling technique. Data collection uses questionnaires. Results: The result of the research indicates that knowledge is good as 87 people (64,0%), with female respondents has good knowledge level of 45 people (33,1%), and based on the most source of information is school as many as 60 people (44,1%). The result of attitude test is good as many as 78 people (57,4%) and result of action test is enough counted 69 people (50,7%). Conclusion: Based on this research can be concluded that students of class X & XI IPA in SMA Negeri 1 Kabanjahe have knowledge level, good attitude and enough action against AIDS.